LPTO-09. INTRATHECAL TOPOTECAN FOR LEPTOMENINGEAL METASTASIS IN SOLID TUMORS: THE MD ANDERSON EXPERIENCE. (12th August 2019) - Sinicrope, Kaylyn D; Barata, Pedro; Walker, Julie; Tremont-Lukats, Ivo W; Groves, Morris; Loghin, Monica; Seligman, Christa; Ferguson, Sherise; Weathers, Shiao-Pei; Penas-Prado, Marta; Kamiya-Matsuoka, Carlos; Harrison, Rebecca; et al.
Abstract: BACKGROUND: Leptomeningeal metastasis (LM) is a devastating complication of cancer resulting in progressive neurologic decline. Although intrathecal (IT) methotrexate and cytarabine are commonly used for solid tumor LM, we routinely use IT topotecan due to previously demonstrated similar efficacy and modest side effect profile. We report updated data on our experience. METHODS: We reviewed clinical records of patients with solid tumor LM treated with IT topotecan at MD Anderson Cancer Center from 2008–2018. Patient characteristics and course were summarized by descriptive statistics. Overall survival (OS) was estimated with Kaplan-Meier, and the association of KPS with OS evaluated with log-rank test. RESULTS: 138 patients were treated with IT topotecan. The median age was 54 years (range, 22–76), 81% were female. Breast cancer (62%) was the most common primary, then lung (21%), melanoma (4%). Median time from primary diagnosis to LM was 3.4 (range, 0.07–25.2) years. LM was diagnosed by CSF cytology alone in 8 (6%), MRI alone in 21 (15%), CSF+MRI in 108 (78%). Patients most commonly presented with headache (39%) or sensory changes (18%), and had a median KPS of 80 (range, 60–100). 66% had prior/concurrent brain metastasis. 71 patients (52%) received WBRT following LM diagnosis. 41% had adverse effects, most commonly nausea/vomiting (22%) and headache (20%). The majority were grade 1 (63%); 7 were grade 4 (2 Ommaya malfunctions and 5 infections). Patients received a median of 9 (range, 1–79) doses, most stopped due to CNS progression (42%). Median OS was 6.5 months (95% CI 4.7, 7.8). OS was 3.8 mos with KPS ≤70, vs. 7.5 mos with KPS >70 (p< 0.001). CONCLUSIONS: IT topotecan has a modest side effect profile. Patients with higher functional status at diagnosis had significantly better survival. This study supports the continued use of IT topotecan as a well-tolerated option for LM.